2007
DOI: 10.1007/s10750-007-9056-7
|View full text |Cite
|
Sign up to set email alerts
|

Different tolerances and responses to low temperature and darkness between waterbloom forming cyanobacterium Microcystis and a green alga Scenedesmus

Abstract: The dynamics of planktonic cyanobacteria in eutrophicated freshwaters play an important role in formation of annual summer blooms, yet overwintering mechanisms of these water bloom forming cyanobacteria remain unknown. The responses to darkness and low temperature of three strains (unicellular Microcystis aeruginosa FACHB-905, colonial M. aeruginosa FACHB-938, and a green alga Scenedesmus quadricauda FACHB-45) were investigated in the present study. After a 30-day incubation under darkness and low temperature,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 38 publications
(48 reference statements)
2
44
0
Order By: Relevance
“…Whereas some species of marine phytoplankton adapt to the dark by reducing their metabolism to a lower level of activity (type I cells), other species maintain unchanged metabolic activity (type II) (Jochem, 1999). As has been suggested by other authors (Zhang et al, 2007;Wu et al, 2008) and confirmed by our study, M. aeruginosa can be included in the former group, since its metabolic activity (measured as fluorescein fluorescence after FDA hydrolysis) decreases in darkness. The results of our study also proved that the addition of H 2 O 2 to cyanobacterial cell suspensions can inhibit metabolic activity regardless of the experimental regime.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Whereas some species of marine phytoplankton adapt to the dark by reducing their metabolism to a lower level of activity (type I cells), other species maintain unchanged metabolic activity (type II) (Jochem, 1999). As has been suggested by other authors (Zhang et al, 2007;Wu et al, 2008) and confirmed by our study, M. aeruginosa can be included in the former group, since its metabolic activity (measured as fluorescein fluorescence after FDA hydrolysis) decreases in darkness. The results of our study also proved that the addition of H 2 O 2 to cyanobacterial cell suspensions can inhibit metabolic activity regardless of the experimental regime.…”
Section: Discussionsupporting
confidence: 77%
“…In the past ten years, esterase activity has been monitored not only in several studies evaluating pollutant toxicity in green algae and cyanobacteria (Franklin et al, 2001;Regel et al, 2002;Hadjoudja et al, 2009;Jamers et al, 2009), but also in studies of the influence of environmental factors such as temperature, darkness or nutrient limitation (Jochem, 1999;Brookes et al, 2000;Wu et al, 2008). It has been demonstrated that there are two distinct types of metabolic response among phytoplankton species exposed to prolonged darkness.…”
Section: Discussionmentioning
confidence: 99%
“…Light response curve and electrons transport rate of the three cyanobacterial strains in the exponential growth phase were measured with a pulse-amplitude-modulated fluorescence monitoring system (PAM, Walz, Effeltrich, Germany). The method was conducted according to the description by Wu et al (2008). The electron transport rate of PS II (ETR) was calculated as: relative…”
Section: Photosynthetic Parameters Measurementsmentioning
confidence: 99%
“…Temperature may directly and indirectly affect photosynthesis, respiration, growth rate, optical properties, and community succession of phytoplankton (Stramski et al 2002;Bouman et al 2003;Elliott et al 2006;Wu et al 2008;Schabh€ uttl et al 2013). At low temperature, the growth and photosynthesis were consistently inhibited.…”
Section: Introductionmentioning
confidence: 99%